1997
DOI: 10.1177/000331979704800705
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Costs of Venous Diseases in Central Italy

Abstract: The Prevalence of Early Atherosclerosis study aims to define the prevalence of subclinical atherosclerosis in a typical population of central Italy. A concomitant study evaluates the prevalence of venous diseases. The prevalence of superficial and deep venous disease, the prevalence of venous thrombosis and pulmonary embolism, and the prevalence of the most common venous malformations were studied through use of medical history, a questionnaire, and noninvasive investigations. The costs of venous problems were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
5

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 1 publication
0
15
0
5
Order By: Relevance
“…In addition, investigators were advised that asymptomatic perfusion defects are frequent findings when patients with proximal DVT have routine lung scans and should not alter clinical management. 15 The protocol required patients to continue with study medications after mean day 21 (range, 18 to 26) if local review of the CCUS and lung scan results found no deterioration. However, continued study treatment was subject to the investigator's clinical judgment if local adjudication suggested asymptomatic deterioration.…”
Section: Study Proceduresmentioning
confidence: 99%
“…In addition, investigators were advised that asymptomatic perfusion defects are frequent findings when patients with proximal DVT have routine lung scans and should not alter clinical management. 15 The protocol required patients to continue with study medications after mean day 21 (range, 18 to 26) if local review of the CCUS and lung scan results found no deterioration. However, continued study treatment was subject to the investigator's clinical judgment if local adjudication suggested asymptomatic deterioration.…”
Section: Study Proceduresmentioning
confidence: 99%
“…Consequently, skin trophic lesions are reduced 5 and these patients present clinical improvements, enabling them to return to their social and labor activities, contributing to reduced socioeconomic costs 6,18 . For these reasons, higher investments in the surgical treatment of varicose veins are required to minimize or solve the problem.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the early performance of such surgical correction can many times prevent venous diseases and reduce treatment costs 6 . With the purpose of expanding the access of the National Healthcare System (SUS) user to elective surgery, and knowing that venous diseases were potentially limiting the citizen's entry and/or stay in the labor market, the Ministry of Health (MS), through Decree 279, on April 7, 1999, created the National Campaign of Elective Surgery, for patients with lower limb varicose veins, cataract, inguinal hernia and prostate diseases 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…Lorenzo Pradelli (1) Farmeconomia e percorsi terapeutici 2008; 9(1): [27][28][29][30][31][32][33][34][35][36][37][38][39][40] composta da piastrine e da fibrina, nella quale restano inglobate cellule ematiche.…”
Section: Parnaparin: Review Della Letteraturaunclassified